Hydrogeological Aspects of the Municipal Water Supply of Albania: Situation and Problems - Romeo Eftimi; Kastriot Shehu; Franko Sara (Hydrology, 2023)
The municipal water supply, related mainly to the cities of Albania, began to develop in the second half of the 19th century and very intensively after 1945. Today, the reported mean water production for the cities, on average, is about 300 l/capita/d, including drinking and industrial water supplies. The territory of Albania has an uneven distribution of very heterogeneous aquifers conditioning often the difficulty of municipal water supply solutions. In this article, are analyzed and classified the hydrogeological aspects of the water supply sources of the settlements, which are summarized in five groups: (a) wells in alluvial intergranular aquifers; (b) karst springs; (c) wells in karst aquifers; (d) springs in fissured rocks; and (e) mixed water sources. For each group of the water supply sources, the main concerns regarding the quantity and quality problems are analyzed, facilitated by the description of a variety of representative examples of different situations. Based on the gained experience, important recommendations are given for the better understanding of hydrogeological aspects of water supply systems, related to the river water recharge areas, the seawater intrusion in coastal aquifers, and the high vulnerability of karst aquifers, as well as transboundary aquifers. However, the main problem of public water supply of Albania remains the poor management of water supply systems, which is reflected in the significant water losses, as well as the low public awareness of requests for sustainable use.